Neuromuscular electrical stimulation promotes development in mice of mature human muscle from immortalized human myoblasts. Issue 1 (December 2015) - Sakellariou, Paraskevi; O'Neill, Andrea; Mueller, Amber; Stadler, Guido; Wright, Woodring; Roche, Joseph; Bloch, Robert
Abstract Background Studies of the pathogenic mechanisms underlying human myopathies and muscular dystrophies often require animal models, but models of some human diseases are not yet available. Methods to promote the engraftment and development of myogenic cells from individuals with such diseases in mice would accelerate such studies and also provide a useful tool for testing therapeutics. Here, we investigate the ability of immortalized human myogenic precursor cells (hMPCs) to form mature human myofibers following implantation into the hindlimbs of non-obese diabetic-Rag1 null IL2rγ null (NOD-Rag)-immunodeficient mice. Results We report that hindlimbs of NOD-Rag mice that are X-irradiated, treated with cardiotoxin, and then injected with immortalized control hMPCs or hMPCs from an individual with facioscapulohumeral muscular dystrophy (FSHD) develop mature human myofibers. Furthermore, intermittent neuromuscular electrical stimulation (iNMES) of the peroneal nerve of the engrafted limb enhances the development of mature fibers in the grafts formed by both immortal cell lines. With control cells, iNMES increases the number and size of the human myofibers that form and promotes closer fiber-to-fiber packing. The human myofibers in the graft are innervated, fully differentiated, and minimally contaminated with murine myonuclei. Conclusions Our results indicate that control and FSHD human myofibers can form in mice engrafted with hMPCs and that iNMES enhances engraftment and subsequent development of mature human muscle.